Desenvolvimento e padronização de um estímulo verbal utilizado para evocar potenciais auditivos de estado estável - Carnaúba, Aline Tenório Lins (2018)
Given that auditory system integrity influences the development of language aspects and that understanding auditory and speech alterations provides important data for selecting appropriate interventions, we proposed to develop technological resources to assess auditory evoked potentials with verbal stimuli. First, a theoretical reference search was conducted, followed by production of the verbal stimulus. Next, the verbal stimulus produced was tested in order to confirm its ability to elicit auditory steady-state evoked potentials. Considering the lack of equipment that could facilitate the use of verbal stimuli, we perceived the need to create a device capable of evoking these stimuli with the interference or not of noise. Accordingly, we obtained a patent for a clinical accessory to enable differential diagnosis between speech and auditory alterations. Finally, after preliminary tests, a company was contracted to manufacture the product. It was concluded that a verbal stimulus can elicit auditory steady-state evoked potentials, but the functionality of the devices available on the market is restricted. With the final prototype, the aforementioned problems may be overcome, since the device in question will make it possible to use more complex stimuli during testing, and help elucidate the physiological processes involved in speech comprehension, enhancing diagnostic accuracy.